Implementasi Website Pondok Pesantren Syafa’atul Qur’an Cilacap - Andesita Prihantara; Nur Wahyu Rahadi; Isa Bahroni; Aris Tjahyanto (Madani : Indonesian Journal of Civil Society, 2019)
Syafatul Qur'ant Islamic Boarding School Pondok Pesantren is an Islamic boarding school institution which in addition has the function of preaching to the community, is also an educational organization that has important and complex information to be known to the public so as to support its existence. The media information used so far is brochures, where the media information is still not optimal in its distribution and requires a large cost and a longer time. Cilacap Syafa'atul Qur'an Islamic Boarding School is not widely known by the general public because it is only in its third year, so it needs promotional media as a means to provide information to the public to find out about the activities in the Syafa'atul Qur'an Islamic Boarding School. Cilacap. Utilizing the Internet and implementing a web-based information system for Syafa’atul Qur'an Cilacap Islamic Boarding School using PHP programming, making it easier for people to obtain more complete information, so that it can be more effective and efficient with the use of information technology. The information presented on this website includes the boarding school company profile, detailed information for each education unit including facilities and student achievements. As an up to date media information, an announcement page and pesantren news are also provided. While for the purpose of da'wah provided a tausiyah page and question and answer